1991
DOI: 10.1002/clc.4960140506
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic and neuroendocrine response to acute administration of the phosphodiesterase inhibitor BM 14.478 in patients with congestive heart failure

Abstract: : The benzimidazol analogue BM 14.478 is a phosphodiesterase inhibitor with both vasodilator and positive inotropic properties. Hemodynamic parameters and plasma hormone levels of 8 patients (1 female, 7 male) with chronic congestive heart failure NYHA Classes II‐IV (1 patient with coronary artery disease, 7 patients with primary dilated cardiomyopathy) were assessed before and until 6 h after the intravenous application of 1.0 mg BM 14.478. There was a significant decrease of mean pulmonary artery pressure (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…On the other hand, elevated cAMP levels enables L-type Ca2+ channels and a component of a delayed-rectifier potassium channel signal transduction pathway in the sinoatrial node (Kodama-Takahashi et al, 2003). Therefore, drugs that inhibit PDE 3 pathways would cause a positive chronotropic effect and inotropic action which have been demonstrated to increase left ventricular ejection fraction and stroke volume (Baim et al, 1983; Jaski et al, 1985; Rauch et al, 1991). However, clinical studies [such as the Prospective Randomized Milrinone Survival Evaluation (PROMISE) (Packer et al, 1991) and the Vesnarinone trial (VEST) (Feldman et al, 1993) studies] have evaluated the long-term effects of PDE 3 administration in congestive HF patients and reported increased cardiovascular mortality.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, elevated cAMP levels enables L-type Ca2+ channels and a component of a delayed-rectifier potassium channel signal transduction pathway in the sinoatrial node (Kodama-Takahashi et al, 2003). Therefore, drugs that inhibit PDE 3 pathways would cause a positive chronotropic effect and inotropic action which have been demonstrated to increase left ventricular ejection fraction and stroke volume (Baim et al, 1983; Jaski et al, 1985; Rauch et al, 1991). However, clinical studies [such as the Prospective Randomized Milrinone Survival Evaluation (PROMISE) (Packer et al, 1991) and the Vesnarinone trial (VEST) (Feldman et al, 1993) studies] have evaluated the long-term effects of PDE 3 administration in congestive HF patients and reported increased cardiovascular mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The binding of this increased cytoplasmic Ca 2þ concentration to troponin C activates actin-myosin cross-bridge formation, thus, eliciting the contractile function [25]. In many studies, the benefits of inotropic action of PDE3 inhibitors such as amrinone, enoximone and milrinone in chronic heart failure patients have been demonstrated, for example, the reduction of left ventricular end-diastolic pressure and the increase in ejection fraction and stroke volume [26][27][28][29][30][31]. It has been observed that the use of PDE3 inhibitors actually produce desirable effects in the short term, however, deleterious effects arise over time [26][27][28].…”
Section: Phosphodiesterase 3 Inhibitor and The Heartmentioning
confidence: 98%